Meningkatkan Kapabilitas Financial UMKM Melalui Rancangan dan Pengelolaan Keuangan di Kecamatan Sidayu - Bintan Fitriyah, Duta; Albar, Kholid; Arifiansyah, Farhadi (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
This service aims to evaluate efforts to improve the financial capability of Micro, Small and Medium Enterprises (MSMEs) in Sidayu District through interventions in drafting and good financial management. The service method used is training and mentoring for 1 month to 35 MSME players in the area. The results of the service showed that there was a significant increase in the ability of MSME financial bookkeeping, from 35% before the program to 78% after the program. In addition, the proportion of MSMEs that have a written financial plan also increased from 22% to 63%. Another interesting phenomenon is the increase in MSME access to formal capital sources, from 28% before the program to 54% after the program. These findings indicate that financial design and management interventions can improve the financial capability of MSMEs, which in turn promotes financial inclusion at the micro enterprise level.